Dancing in Shackles: The Double-Edged Sword Effect of Felt Accountability on Work Outcomes and Individual Wellbeing - Li, You; Liu, Wei; Yu, Guangtao (Frontiers in Psychology, 2022)
Accountability is a core element for groups and societies to operate efficiently. However, there have been confusing findings in previous studies on felt accountability, and few efforts have been made to clarify its complicated role. Drawing on self-determination theory, we developed an integrative model to examine the double-edged sword effect of felt accountability on work outcomes and individual wellbeing. We utilized a three-wave sample of 294 employees to test our hypotheses. The findings supported our hypotheses. Specifically, felt accountability is positively related to both task performance and emotional exhaustion, and obsessive passion mediates the positive relationship between felt accountability and task performance, while work overload mediates the positive relationship between felt accountability and emotional exhaustion. This study integrates the positive and dark sides of felt accountability, provides new insights into its mechanism and expands the application of self-determination theory.